Pino híbrido y respuesta a heladas: ¿plantines de cutting o de semilla? Un análisis preliminar de parámetros fisiológicos = Hybrid pine and frost response: cutting or seedling? A preliminary analysis of physiological parameters - Schoffen, Cristian Damián; Bulfe, Nardia María; Fernandez, María Elena; Martinez Meier, Alejandro (Facultad de Ciencias Forestales, Universidad Nacional de Misiones., 2025)
Preliminary results are presented comparing the growth and physiological variables related with frost tolerance in plants of hybrid pine of cutting and seedling origin (here named “materials”). Significant differences were found between sites / materials, in initial size of plants (height and basal diameter), with cutting plants being larger than cuttings. However, the relative growth was higher in seedling-origin plants, both in height and basal diameter. Damage to the cell membrane due to frost exposition in the lab was lower after a field frost event than in previous dates in both hybrids materials, indicating acclimation to frost. But the acclimation was higher (i.e. the damage was lower) in the seedling origin. Branch vulnerability to cavitation due to frost did not differ between materials, but elastic and osmotic adjustment of leaf tissues presented different behaviors. The installation of new field trials and incorporation of new variables is considered.